1986
DOI: 10.2134/agronj1986.00021962007800020012x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Nitrogen and Water Stresses on Water Relations of Field‐Grown Corn Leaves1

Abstract: Water and N stresses often limit corn (Zea mays L.) grain yields. Although the effects of either water or N stress on crop growth and development, physiology, and yield have been widely studied, relatively little information is available on the interactive effects of these stresses when imposed in combination. The objective of this study was to define and evaluate the interactive effects of water and N stresses on leaf water potential components, transpiration rate, and stomatal resistance of field-grown corn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 5 publications
(7 reference statements)
3
23
0
Order By: Relevance
“…Maize water relations during water stress have been extensively documented (e.g. Bennett et al 1986Bennett et al , 1987Tyree et al 1986;Tardieu et al 1992). The relationships between relative soil water content (RSWC), leaf water potential (Y leaf ) and leaf water loss (E) reported in this study are consistent with the data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Maize water relations during water stress have been extensively documented (e.g. Bennett et al 1986Bennett et al , 1987Tyree et al 1986;Tardieu et al 1992). The relationships between relative soil water content (RSWC), leaf water potential (Y leaf ) and leaf water loss (E) reported in this study are consistent with the data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that the capacity for osmotic adjustment increased in plants with increasing N supply (e.g. Bennett et al 1986;Garcia, Fuentes & Gallego 1996;Harvey 1997;DaMatta et al 2002).…”
Section: Hydraulic Architecture and Plant Water Relationsmentioning
confidence: 93%
“…However, the N status has variable effects on plant water relations. For example, Morgan (1986) found that in wheat a greater amplitude of osmotic adjustment was associated with low N supply after withholding watering, while opposite responses in corn (Bennett et al 1986) and tomato (García et al 1996) have been observed. Furthermore, while N or water deficits usually decrease the rate of carbon assimilation (A), N limitation per se may affect stomatal behaviour in different ways; both increases (e.g., Livingston et al 1999) and decreases (e.g., Lima et al 1999) in stomatal conductance (g s ) have been noted.…”
Section: Introductionmentioning
confidence: 99%